2001
DOI: 10.1002/bmc.44
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of assay method for DX‐8951 and its metabolite in human plasma and urine by high‐performance liquid chromatography/atmospheric pressure chemical ionization tandem mass spectrometry

Abstract: A new liquid chromatographic/mass spectrometric assay has been developed for the determination of DX-8951, a new anti-tumor drug, and its 4-hydroxymethyl metabolite (UM-1) in human plasma and urine. Solid-phase extractions were used for sample preparation. A gradient reverse-phase HPLC separation was developed with mobile phases consisting of trifluoroacetic acid and methanol. The detection was conducted using atmospheric pressure chemical ionization tandem mass spectrometry in the selected reaction monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It is thought that the sensitivity of HPLC is not adequate to analyze tissue samples, and the total analysis time is relatively long. Furthermore, we have developed an LC/MS/MS method for the determination of DX-8951 in human plasma (Oguma et al, 2001b). It is suggested that the use of this LC/ MS/MS method enables the chromatographic run time to be reduced, and is applicable for analyzing both released free drugs and conjugated drug in tumor tissue.…”
Section: Methodsmentioning
confidence: 99%
“…It is thought that the sensitivity of HPLC is not adequate to analyze tissue samples, and the total analysis time is relatively long. Furthermore, we have developed an LC/MS/MS method for the determination of DX-8951 in human plasma (Oguma et al, 2001b). It is suggested that the use of this LC/ MS/MS method enables the chromatographic run time to be reduced, and is applicable for analyzing both released free drugs and conjugated drug in tumor tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma samples were analyzed at MDS Pharma Services (Montreal, Canada). Total DX-8951 plasma concentrations were quantified using a validated high-performance liquid chromatography method [17,18]. The lower limit of quantitation was 0.201 ng/mL.…”
Section: Blood Sampling Schedule and Analytical Assaymentioning
confidence: 99%
“…There are several liquid-liquid extraction approaches available for simultaneous measurement of the δ-lactone and δ-hydroxy acid forms of various CPTs in human plasma (Beijnen et al, 1993;Li and Zhang, 1996;Warner and Burke, 1997;Loos et al, 1997;Sparreboom et al, 1998a;Sai et al, 2002). Solid phase extraction (Barilero et al, 1992;Takimoto et al, 1994;Oguma et al, 2000Oguma et al, , 2001 and restricted access media methodologies have been recently reported (Ma et al, 2002) for simultaneous determination of these CPT forms in human plasma. All of these methods require immediate sample processing in order to avoid inter-conversion between the two forms.…”
Section: Introductionmentioning
confidence: 98%